El uso de los libros de texto en la enseñanza secundaria: Lo que los profesores opinan (ING) - Murillo, Mario (2003)
It is inconceivable that a mathematics class be given without the support of any written material, usually a textbook. A good textbook will contain the necessary subject matter as well as exercises. This paper examines some issues concerning the textbook and its used by High School teachers, following  a survey conducted by the Centro de Investigaciones Matemáticas y Meta-Matemáticas in 2001.